GPS station short-term dynamic characteristics of micro displacement before Menyuan M6.4 earthquake - Wei Feng; Jinwei Ren; Zaisen Jiang (Geodesy and Geodynamics, 2016)
Continuous observation data from 24 GPS stations are selected in the area (33.0°N–41.0°N, 95.0°E–105.0°E) for this study (the period is from Jan. 1, 2015 to Jan. 20, 2016). Three components, NS, EW and UD, of the daily solutions are filtered by the Hilbert–Huang transform (HHT) with frequency band of 5.787 × 10−7–7.716 × 10−8 Hz (20–150 days in period). And short-term dynamic characteristics of micro displacement before Menyuan M6.4 earthquake are studied by using the temporal dependencies and cross spectrum analysis. The results show that before the earthquake the horizontal undulatory motions are higher than the average level in the series data which indicate the disturbance feature of regional stress before the earthquake. Three GPS stations on Qinghai-Tibet Plateau with their setting perpendicular to the seismogenic fault have consistent movement. The increase of amplitude of the horizontal micro motion observed before the quake is conducive to the earthquake occurrence. However, we could not be sure if the undulatory motion triggered the earthquake. It is quite necessary to build more GPS continuous observation stations and optimize the monitoring network so as to improve the understanding of the short-term dynamic crustal variation before earthquake.